The fate of the passbook: Why it vanished in the US but survived in Germany during the stagflation period (1966-1983) - Sebastian Knake (Humboldt University Berlin, 2024)
In his article, Sebastian Knake challenges the general assumption that traditional savings accounts in the US disappeared naturally as a result of the combination of interest rate regulation and extraordinarily high market interest rates during the stagflation period. By comparing the US experience with simultaneous developments in West Germany, he finds that the opportunity costs of owning a regular passbook were comparable in both countries. In contrast to the US case, however, the passbook remained a cornerstone of household saving in Germany. Drawing upon research in several bank archives in the US and Germany, Knake explains these divergent developments in terms of fundamental differences in how banks and their customers communicated over prices. In the US, a peculiar combination of regulative rules forced banks, and especially savings institutions, to aggressively promote new types of bank accounts that were introduced by federal regulation authorities, thereby increasing nominal interest rate expectations. In Germany, by contrast, banks confined information about advantageous investment opportunities to the smallest possible share of the customer base. These divergent communication strategies reflect a difference in the balance of power in the bank-customer relationship. German customers depended on their primary-and in most cases only-bank relationship to acquire information on alternative investments, while US customers could draw on several relationships with banks and savings institutions to obtain the relevant information. Thus, the fate of the passbook was sealed by the ability or inability of banks to keep their customers in the dark about the real opportunity costs of passbook saving.
urn:nbn:de:kobv:11-110-18452/29936-3
Keywords: G14; G21; N20; N22; N24; 330; Savings; Deposits; Interest Expectations; Portfolio Choice; Financial History; Passbook; Comparative History